Strategi Coping pada Ibu Bekerja yang Memiliki Anak Balita - Annafi Fahdulla Alam; Agitia Kurniati Asrila (PT. PENERBIT TIGA MUTIARA, 2026)
Working mothers with toddlers face dual-role demands that may lead to psychological distress, role conflict, and difficulties in maintaining a balance between work and childcare responsibilities. These challenges make coping strategies an essential factor in supporting mothers' psychological well-being. This study aims to analyze the coping strategies employed by working mothers with toddlers and identify the factors influencing their selection of coping strategies. The study employed a descriptive qualitative approach using purposive sampling to recruit working mothers with children under five years of age employed at a Correctional Center. Data were collected through in-depth interviews and analyzed using the Miles and Huberman interactive model, while data trustworthiness was ensured through source triangulation and member checking. The findings indicate that the coping strategies adopted by participants include social support, emotional regulation, relaxation activities, and the development of positive perspectives toward work and childcare responsibilities. The selection of these strategies is influenced by family support, personal experiences, job characteristics, the work environment, and individuals' ability to adapt to various demands. The study concludes that the successful management of dual roles among working mothers depends on their ability to integrate multiple coping strategies adaptively according to the situations they encounter. The novelty of this study lies in revealing coping strategies as an adaptive process that integrates social support, emotional regulation, relaxation activities, and positive perceptions of the work environment as part of maintaining a balance between occupational responsibilities and childcare.